Prevalence and Risk Assessment of Obstructive Sleep Apnea in Myasthenia Gravis Patients Using the STOP-BANG Questionnaire - Mi-Ri Kang; Seong-il Oh; Ki-Hwan Ji (Sleep Medicine Research)
Myasthenia gravis (MG) is an autoimmune disorder leading to muscle weakness and fatigue, with limited research on its association with obstructive sleep apnea (OSA). This study evaluated the prevalence and risk of OSA in 72 Korean patients diagnosed with MG, utilizing the STOP-BANG questionnaire. Participants were categorized into low-risk and intermediate to high-risk groups. Additional evaluations included the Epworth Sleepiness Scale (ESS), Myasthenia Gravis Activities of Daily Living (MG-ADL), and the Revised Scale of 15-Item Myasthenia Gravis Quality of Life Scale (MG-QOL15r). The results indicated that 52 MG patients (79.2%) fell into the intermediate to high-risk category for OSA, with significantly higher ESS scores observed in this group compared to those at low risk (6.73±5.15 vs. 3.40±3.98, p=0.023). However, traditional OSA risk factors such as age, sex, and body mass index, as well as scores on MG-ADL and MG-QOL15r, did not show significant differences between groups. This study underscores a considerable prevalence of OSA risk among Korean patients with MG, with notable correlations between higher STOP-BANG scores and increased daytime sleepiness.